PELAKSANAAN PENAWARAN TENDER DALAM PASAR MODAL DAN AKIBAT HUKUMNYA DI INDONESIA - Pasaribu, Abigail Frida Christine Chiquita (Justitia et Pax, 2020)
The problem of Tender Offer is sticking to the surface, among others, because there have been several cases involving the Takeover of a Public Company by another Party, thus causing losses to other Shareholders, especially the Public Shareholders. This study aims to determine the arrangement of Tender Offers in Indonesia and the impact of the Takeover on a Public Company that was taken over. The form of research in the writing of this journal is normative legal research using the statutory approach. The legal materials used are of two types, namely primary legal materials and secondary legal materials. The results of this research are: First, Mandatory Tender Offer is regulated in POJK No. 9/POJK.04/2018. There is a provision that the Controllers must refloate within two years if the share ownership exceeds 80% as a result of the Mandatory Tender Offer. Then, the Voluntary Tender Offer is regulated in POJK No. 54/POJK.04/2015 concerning Voluntary Tender Offer. In general, the background to the Voluntary Tender Offer is that the Target Company plans to be delisted, as well as changing its status to a Private Company (Go Private). Also, the Voluntary Tender Offer can be made if the Bidder wishes to increase its investment portfolio and assesses that the Target Company has the potential to continue to develop in the future. Second, Takeovers can have legal consequences on the status of the company, company controllers, and employment.